ANALISIS PENGARUH DESENTRALISASI FISKAL, INVESTASI DAN PENDUDUK TERHADAP PRODUK DOMESTIK REGIONAL BRUTO, KAPASITAS FISKAL DAN PENGELUARAN PEMERINTAH DAERAH DI PROVINSI PAPUA - Dewi Adhityarani Musaidah; Ida Ayu Purba Riani; Elsyan Rienette Marlissa (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
This study aims to answer how the influence of fiscal capacity, regional government spending, investment and the residents to regional gross domestic product (GDP) and fiscal capacity of regional government spending. There are seven exogenous variables, three endogenous variables analyzed use the Two Stage Least Square (2SLS), that produces simultaneous estimation equation model. The result showed fiscal capacity, regional government spending, foreign investment, domestic investment, and residents simultaneously significant to the regional GDP. The second model, the fiscal capacity of regional GDP, local taxes, and levies, simultaneously significant to fiscal capacity. The third model, regional government spending show the regional GDP, fiscal capacity, local revenue, balance funds, and residents simultaneously will not affect local government spending. Keywords: Fiscal decentralization, investment, Residents, regional gross domestic product, fiscal capacity, provinces of papua government spending.